Edukasi Melalui Kegiatan Penyuluhan Pemanfaatan Digital Marketing Di Lapas Kelas IIB Takalar - Seppa, Yusi Irensi; Maya Kasmita; Muhammad Luthfi Siraj; Aris Baharuddin; Siti Syarifah Wafiqah Wardah (Jurusan Teknik Informatika dan Komputer, 2023)
This community service activity takes the form of socialization, education and counseling targeting inmates at the Class IIB Takalar Prison. This community service aims to provide knowledge and understanding to residents of the Class IIB Takalar Prison regarding the use of digital marketing. The location of this service was carried out at the Class IIB Takalar Prison. The method used is to give a lecture in the first session, then the second session is a discussion with questions and answers, then the last session is an evaluation. The evaluation results obtained were by brain color tests from 20 prison inmates. The evaluation results showed that 7 people met the criteria for the yellow brain type, 2 people met the criteria for the blue brain type, 4 people met the criteria for the green brain type, and 7 people met the criteria for the orange brain type. This test shows the personality type related to entrepreneurial character based on thought patterns and ways of acting. By knowing the multi-faceted nature of personality, it allows people to accept, respect and appreciate others more easily. The result of this service activity is to increase the understanding of the inmates of Class IIB Takalar Prison regarding the use of digital marketing so that they can produce output and master digital marketing.